REKOMENDASI PERAWATAN KOMPONEN AIR CYCLE MACHINE (ACM) PADA PESAWAT B737-900ER - Anisafitri, Berni; Rahmawati, Fajar Khanif; Mulyani, Sri (Institut Teknologi Dirgantara Adisutjipto, 2023)
Analysis with the Weibull distribution method shows that the right treatment recommendations for treating air cycle machine (ACM) in the form of category preventive maintenancetime directed (TD), due to category preventive maintenanceTime Directed (TD) is a category of preventive maintenance that can be carried out if the time variable of a component or system is known and directly aims to prevent damage.